Analisis Yuridis terhadap Hambatan Penegakan Hukum dalam Kasus Pelanggaran Etika Profesi Tenaga Kesehatan di Indonesia - Sri Nur Damayana (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Professional ethics is not only a moral guideline for health workers, but is also an integral part of the legal system that regulates the relationship between health workers, patients and society. In a legal context, professional ethics is the foundation that guarantees that every action of health workers is carried out in accordance with professional standards and aims to protect patient rights. The aim of this research is to analyze the obstacles and impact of obstacles faced in law enforcement on violations of professional ethics for health workers in Indonesia. The research method used is normative research, using secondary data. The research results show that obstacles to law enforcement against violations of professional ethics for health workers in Indonesia stem from various factors, such as weak regulations, lack of coordination between institutions, slow and complicated legal processes, and minimal understanding of ethics and law among health workers. Furthermore, there is a significant impact on the protection of patient rights and the professionalism of health workers in Indonesia. On the one hand, patients become vulnerable to violations of their rights, such as the right to safe and quality medical services.